MENINGKATKAN KEMAMPUAN SOSIAL MELALUI PEMBELAJARAN KOOPERATIF MODEL JIGSAW PADA ANAK KELAS B1 DI TK LABOR FKIP UNRI KECAMATAN TAMPAN KOTA PEKANBARU - Nita Budi Astuti; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to improve the social skills of children B1 class in TK Labor Fkip Unri Tampan district Pekanbaru city through cooperative learning model of jigsaw. This research is a classroom action research that uses 2 cycles. The population and sample in this study were all children in class B1 in TK Labor Fkip Unri Tampan district Pekanbaru city with the number of children 20 people consisting of 11 girls and 9 boys. The data collection tool used in the study improved the social skills of children through cooperative learning of the jigsaw model using an observation sheet. This study uses qualitative descriptive analysis technique that is performed data analysis techniques of data reduction, data presentation and conclusion. The survey results revealed by the improvement that occurred from before their actions and an increase from cycle to cycle. If in the first cycle there is an increase, the research is not continued, but if the first cycle does not improve, the research will continue to cycle II. If in the second cycle there has been an increase, the research is considered successful.Key Words: Social Ability, Jigsaw Model Cooperative Learning